The Short Term Influence of Chest Physiotherapy on Lung Function Parameters in Children With Cystic Fibrosis and Primary Ciliary Dyskinesia - Vandervoort, Bjarne; De Beuckeleer, Django; Huenaerts, Elke; Schulte, Marianne; Vermeulen, François; Proesmans, Marijke; Troosters, Thierry; Vreys, Myriam; Boon, Mieke (Frontiers in Pediatrics, 2022)
Airway clearance therapy (ACT) is one of the basic treatment modalities for patients with bronchiectasis to improve mucociliary clearance. The progression of lung disease in patients with bronchiectasis can be evaluated by spirometry and multiple breath washout (MBW) and it is advised to monitor these on a regular basis. However, the short term effect of ACT on spirometry and MBW parameters is insufficiently clear and this variability may impact standardization. For cystic fibrosis (CF), available literature refutes a short time effect on spirometry and MBW parameters in children, however for primary ciliary dyskinesia (PCD) no data are available. We performed a single-center, prospective cross-over study to evaluate the short term effect of an ACT session using positive expiratory pressure mask on forced expiratory volume in 1 second (FEV1) and lung clearance index (LCI), derived from MBW, compared to no intervention in pediatric patients with CF and PCD. A total of 31 children were included: 14 with PCD and 17 with CF. For the whole group, there was no difference in median change of FEV1 pp between the treatment and the control group (p 0.969), nor in median change of LCI (p 0.294). For CF, the mean change in FEV1 pp with ACT was -1.4% (range -9 to +5) versus -0.2% (range -6 to +5) for no intervention (p 0.271), the mean change in LCI with ACT was +0.10 (range -0.7 to +1.2) versus +0.17 (range -0.5 to +2.8) for no intervention (p 0.814). In PCD, the mean change in FEV1 pp with ACT was +1.0 (range -7 to +8) versus -0.3 (range -6 to +5) for the control group (p 0.293) and the mean change in LCI with ACT was -0.46 (range -3.7 to +0.9) versus -0.11 (range -1.4 to +1.3) for the control group (p 0.178). There was no difference between PCD and CF for change in FEV1 pp after ACT (p= 0.208), nor for LCI (p= 0.095). In this small group of patients, we can’t show evidence of a significant short-term effect of chest physiotherapy on FEV1 pp nor LCI in PCD and CF values nor variability.